TECHNOLOGY FOR DEVELOPING CLINICAL REASONING COMPETENCY AMONG MEDICAL UNIVERSITY STUDENTS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the technology-driven strategies for developing clinical reasoning competency among medical university students. Emphasis is placed on simulation-based education, digital case libraries, problem-based learning, and reflective teaching methods as key tools for fostering critical thinking and diagnostic skills. The integration of virtual patients, e-learning platforms, and structured assessment tools is discussed in relation to their pedagogical value and impact on clinical preparedness. The study highlights the necessity of adopting modern technologies and interactive methodologies to cultivate future physicians' ability to make evidence-based, patient-centered decisions in dynamic clinical environments.